2017
DOI: 10.1177/1362168817744389
|View full text |Cite
|
Sign up to set email alerts
|

TBLT implementation and evaluation: A meta-analysis

Abstract: Task-based language teaching (TBLT) is an empirically investigated pedagogy that has garnered attention from language programs across the globe. TBLT provides an alternative to traditional grammar translation or present-practice-produce pedagogies by emphasizing interaction during authentic tasks. Despite several previous meta-analyses investigating the effect of individual tasks or short-term task-based treatments on second language (L2) development, no studies to date have synthesized the effects of long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(31 citation statements)
references
References 68 publications
0
30
0
1
Order By: Relevance
“…The above four steps using TBLT can encourage students to utilize all four skills of English as a means of communication and successfully accomplish a task. Although a large number of studies have supported the effectiveness of TBLT, there are not enough studies targeting Japanese EFL college students, as Bryfonski and Mckay's (2017) metaanalysis did not include any study targeting L1 Japanese learners. More studies are needed to examine the effectiveness of TBLT on Japanese EFL students, and this paper partially addresses this need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above four steps using TBLT can encourage students to utilize all four skills of English as a means of communication and successfully accomplish a task. Although a large number of studies have supported the effectiveness of TBLT, there are not enough studies targeting Japanese EFL college students, as Bryfonski and Mckay's (2017) metaanalysis did not include any study targeting L1 Japanese learners. More studies are needed to examine the effectiveness of TBLT on Japanese EFL students, and this paper partially addresses this need.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have uncovered the positive effects of TBLT on learners' L2 performance. Bryfonski and McKay (2017) conducted a meta-analysis examining the effects of TBLT implementation in language classrooms. They selected 52 studies based on criteria such as "studies accessible in English" (p. 609) and "studies that examined the effects of the TBLT program's implementation on some outcome measure" (p. 610).…”
Section: Effects Of Tbltmentioning
confidence: 99%
“…While there is an emphasis in TBLT literature on the foreign language learning context (e.g. see Bryfonski & McKay, 2019), the contexts listed below feature less commonly. -the teaching and learning of languages other than English…”
Section: An Under-researched Contextmentioning
confidence: 99%
“…The task-based NA, however, acknowledges language learning as a complex sociocognitive process with a focus on meaningful units, through the identification of the different types of communication tasks that specific communities of learners need to perform in the real world in the target language (Long, 2005(Long, , 2015. Recently, a meta-analysis of TBLT programs and their long-term effect on FL learning demonstrated an overall positive and strong effect (d=0.93) of TBLT as opposed to more traditional pedagogies (Bryfonski & McKay, 2017). The meta-analysis also revealed that stakeholders held positive views regarding such programs.…”
Section: 2mentioning
confidence: 99%